Construction and validation of a scenario for recognizing sepsis by nursing students: a methodological study - Jane Walkíria da Silva Nogueira; Marcia Cristina da Silva Magro (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: To build and validate a clinical simulation scenario for teaching Nursing students about early recognition of signs and symptoms of sepsis in the context of the emergency unit. Methods: Methodological study developed in two phases: construction of a simulated scenario and content validation by expert judges. For data analysis, the Content Validity Index (CVI) was calculated considering agreement equal to or greater than 80%. The minimum acceptable CVI value for scenario validation was 1.0. Results: The simulation scenario proved to be appropriate, with a global Content Validity Index equal to 1. Some adjustments related to the clarity of the wording were necessary, as suggested by the judges. Conclusions: A medium-complexity, high-fidelity scenario was successfully constructed and validated for teaching early recognition of sepsis signs and symptoms.